Dose and time-dependent effect of orange juice on the antimalarial efficacy of artemether-lumefantrine, haematological, and antioxidant parameters - Iregbu, John K.; C. Iregbu, Jessica; Edeh, Gabriel C.; Ajaghaku, Daniel L.; Nwoye, Christian C.; Ashibogwu, Ezinneamaka M.; Njoku, Chukwuemeka C.; Ugwuegbu, Chidera M.; Okafor, Bostock C.; Tony-Okpalaobi, Obinna H.; Okparaeke, Chibuikem E. (International Journal of Research in Medical Sciences, 2025)
Background: Orange juice (OJ) contains ascorbic acid, which has antioxidant properties that would be expected to protect against haemolytic effects and possibly interfere with the antimalarial mechanism of the artemisinin-based combination therapy. This study was designed to investigate the dose and time-dependent effect of OJ on the anti-malarial efficacy of artemether-lumefantrine (AL). Methods: Malaria was induced by inoculating plasmodium berghei parasite through the intraperitoneal route to albino mice. The infection was allowed to establish for 3 days, followed by treatment with AL alone, and its combination with graded doses of OJ. Separate doses of OJ were also administered to different groups. Results: Treatment with AL alone produced total parasite clearance (100%) in days 3 and 4 post-treatment. Co-administration of AL with graded doses of OJ showed significant (p<0.05) increase in parasitemia at OJ combination doses of 10, 8, and 6 ml/kg. Unlike antagonistic combination interaction exhibited by higher combination doses of OJ, lower combination doses of 4 and 2 ml/kg potentiated the antiplasmodial activity of AL. Compared to vehicle (malaria) control group, a significant (p<0.05) increase in PCV was achieved at combination OJ doses of 10, 8, 6, and 4 ml/kg. Combination doses of OJ at 10, 8, 6 ml/kg restored the catalase enzyme activity to the level that exist in uninfected naïve control group. Conclusions: OJ showed both antagonistic and beneficial interactions with AL at higher and lower doses, respectively. Combination of OJ with AL also has a beneficial effect in reducing both parasite and AL-induced oxidative stress.